2015
DOI: 10.1051/0004-6361/201525680
|View full text |Cite
|
Sign up to set email alerts
|

Variations of dose rate observed by MSL/RAD in transit to Mars

Abstract: Aims. To predict the cruise radiation environment related to future human missions to Mars, the correlation between solar modulation potential and the dose rate measured by the Radiation Assessment Detector (RAD) has been analyzed and empirical models have been employed to quantify this correlation. Methods. The instrument RAD, onboard Mars Science Laboratory's (MSL) rover Curiosity, measures a broad spectrum of energetic particles along with the radiation dose rate during the 253-day cruise phase as well as o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 22 publications
2
29
0
1
Order By: Relevance
“…Mulligan et al 2009). Furthermore, a decrease in the abundance of energetic particles associated with FD has also been in situ observed by the Mars Science Laboratory's rover Curiosity, during its cruise phase from Earth to Mars (Guo et al 2015).…”
Section: Introductionmentioning
confidence: 77%
“…Mulligan et al 2009). Furthermore, a decrease in the abundance of energetic particles associated with FD has also been in situ observed by the Mars Science Laboratory's rover Curiosity, during its cruise phase from Earth to Mars (Guo et al 2015).…”
Section: Introductionmentioning
confidence: 77%
“…Without the Martian atmosphere around it, part of the RAD view cone was only very lightly shielded during this period (Zeitlin et al, ) and thus observed a different range of energies in the primary GCR spectrum and a higher number of SEP events. Besides, FDs were also detected during the cruise phase (Guo et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…MSL/RAD is an energetic particle detector and it has been carrying out radiation measurements of both particle types and fluxes together with dose and dose equivalent rates during its 11-month cruise phase (Zeitlin et al 2013;Posner et al 2013;Guo et al 2015a;Ehresmann et al 2016) and later on the surface of Mars since the landing of MSL in August 2012 Ehresmann et al 2014;Rafkin et al 2014;Köhler et al 2014;Wimmer-Schweingruber et al 2015;Guo et al 2015b). On the surface of Mars, RAD measures a mix of primary GCRs or SEPs and secondary particles generated in the atmosphere including both charged ) and neutral (Köhler et al 2014;Guo et al 2017b) particles.…”
Section: Gcr Measurement By Msl/radmentioning
confidence: 99%